Predictive Value of Drug-Induced Sleep Endoscopy (DISE) in Pediatric Obstructive Sleep Apnea: A Multicenter Cohort Study in Indonesia - Sarah Istiqomah; Annisa Annisa; Dessy Agustina; Abhimanyu Putra; Zainal Abidin Hasan; Johan Wirahadi Putro; Venny Melinda; Nabila Saraswati; Made Swastika (Scientific Journal of Pediatrics, 2025)
Introduction: Obstructive sleep apnea (OSA) is a significant pediatric health concern in Indonesia, but diagnostic and treatment pathways are often resource-constrained. Drug-induced sleep endoscopy (DISE) offers a dynamic assessment of upper airway obstruction, but its predictive value for treatment outcomes in Indonesian children remains unclear. This study aimed to evaluate the predictive value of DISE findings for polysomnography (PSG)-determined OSA severity and surgical outcomes in a multicenter cohort of Indonesian children. Methods: A prospective, multicenter cohort study was conducted at three tertiary hospitals in Indonesia. Children aged 2-18 years with suspected OSA underwent DISE and overnight PSG. DISE findings were classified using the VOTE (Velum, Oropharynx, Tongue base, Epiglottis) classification system. The primary outcome was the correlation between DISE findings and the apnea-hypopnea index (AHI) on PSG. Secondary outcomes included the prediction of surgical success (defined as a postoperative AHI < 5 and >50% reduction from baseline) after adenotonsillectomy (T&A). Statistical analyses included Spearman's rank correlation, receiver operating characteristic (ROC) curve analysis, and logistic regression. Results: 250 children (mean age 8.2 ± 3.5 years, 60% male) were included. A significant positive correlation was found between the total VOTE score and AHI (ρ = 0.62, p < 0.001). Tongue base obstruction (VOTE-T) showed the strongest correlation with AHI (ρ = 0.58, p < 0.001). The area under the ROC curve (AUC) for the total VOTE score predicting severe OSA (AHI ≥ 10) was 0.85 (95% CI, 0.79-0.91). In the subgroup of 180 children who underwent T&A, a higher total VOTE score (particularly VOTE-T and VOTE-E scores) was significantly associated with a lower likelihood of surgical success (OR 0.45, 95% CI 0.28-0.72, p = 0.001). Conclusion: DISE, using the VOTE classification, demonstrates good predictive value for OSA severity and surgical outcomes in Indonesian children. Tongue base and epiglottic obstruction are particularly important predictors. DISE can be a valuable tool for guiding treatment decisions in resource-limited settings.